Marketing issues for remanufactured products. (1st August 2019) - Govindan, Kannan; Jiménez-Parra, Beatriz; Rubio, Sergio; Vicente-Molina, María-Azucena
Abstract: Remanufacturing is an industrial process whereby used products are restored to useful life. This special issue seeks to address marketing issues for remanufactured products and provide an in-depth understanding of their barriers, together with mitigating practices and future opportunities. The articles present and analyse opportunities to improve marketing approaches for remanufactured products through exploring various marketing strategies, consumer behaviours, pricing and branding decisions, and optimized green transportation. This editorial note summarizes the outcomes of the papers published under this special issue, in addition to discussions on various influencing factors on marketing issues for remanufactured products including marketing attributes, customer willingness, pricing practices and performance evaluation methods. The final conclusion shows that there is sufficient scope to explore various perspectives connected with the issues of marketing remanufactured products through different fields of application.